2009
DOI: 10.21273/hortsci.44.6.1704
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorous Removal by Ornamental and Wetland Plants in a Greenhouse Recirculation Research System

Abstract: A nutrient recirculation system (NRS) was used to assess the ability of four ornamental and three wetland plant species to remove nitrogen (N) and phosphorous (P) from stormwater runoff. The NRS was filled with a nutrient solution with total N and P concentrations of 11.3 and 3.1 mg·L−1, respectively, to simulate high levels of nutrient contaminations in stormwater. Nutrient removal abilities of herbaceous perennial ornamental plants, canna (Canna × Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Our findings indicate that sweet wormwood had high NUE due to the significantly high nitrogen content which translated to high growth rates than amaranth and pumpkin. Studies using mangroves (Agraz-Hernández et al 2018) wetland plants (Chen et al 2009) have demonstrated that luxury uptake contributes to the removal of nutrients from wastewater. The substantial removal of phosphorus on day 15 in all the hydroponic subsystems can be attributed to increased demand for root development when plants are young, whereas high phosphorus removal efficiency of pumpkin can be an indication of luxury uptake of phosphorus to offset anticipated need during the fruiting stage (Buzby and Lin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that sweet wormwood had high NUE due to the significantly high nitrogen content which translated to high growth rates than amaranth and pumpkin. Studies using mangroves (Agraz-Hernández et al 2018) wetland plants (Chen et al 2009) have demonstrated that luxury uptake contributes to the removal of nutrients from wastewater. The substantial removal of phosphorus on day 15 in all the hydroponic subsystems can be attributed to increased demand for root development when plants are young, whereas high phosphorus removal efficiency of pumpkin can be an indication of luxury uptake of phosphorus to offset anticipated need during the fruiting stage (Buzby and Lin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, excavation reasons and adequacy for removal comparison, belowground biomass sample of T. latifolia was not considered in the present study. Furthermore, aboveground biomass is important in estimating the amount of biomass to be harvested for reuse [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Triclosan is an antibacterial agent found in hand sanitizers, soaps, detergents etc. This study used Typha latifolia, Phragmites australis, and Phalaris arundinacea (Chen et al, 2009). They found a 70% reduction in triclosan at the end of their twelve-month study.…”
Section: Native Macrophytes and Invasive Macrophytesmentioning
confidence: 99%